The Au decoration effect on performance enhancement of photodetector in MoS2 nanosheets - Anahita Taherkhani; Ramin Mohammadkhani (Heliyon, 2025)
Molybdenum disulfide nanostructures (NSs) are created using a thermal chemical vapor deposition method (TCVD). These NSs are then decorated with Au to form Au/MoS2 nano heterojunctions (NHs) using a Physical vapor deposition method. The goal is to create high-performance photodetectors. To study the as-prepared structures, X-ray diffraction, Raman, and UV–Visible spectroscopy are applied to analyze the structural and optical properties. The photodetectors' responsivity (R), detectivity (D), external quantum efficiency (EQE) and stability are then tested using different laser power for incident light at wavelengths of 405 and 635 nm. The results suggest that these devices have the potential for future applications in optoelectronics.